Analyzing classroom interactions focusing on IRF patterns and turn-taking - Hidayatullah, Efendi (Universitas Muhammadiyah Malang, 2024)
This study aims to analyze patterns of interaction and turn-taking in the context of classroom learning using a classroom discourse analysis approach. This research focuses on understanding the communication dynamics between teachers and students and identifying dominant patterns during the learning process. The method used is qualitative, with data collection through observation using video recorder instruments in class XI SMK Muhammadiyah Mertoyudan. The research participants were a teacher and class XI students of SMK Muhammadiyah Mertoyudan, totalling 24 students, consisting of 1 teacher and 23 students. The data results show the sequences developed from the questions between teacher and student interactions. The results of this study support the view that the discursive role of the Feedback sequence in IRF (Initiation-Response-Feedback Sequence) is to develop dialogue between teachers and students. The findings of this study on the IRF pattern are that the teacher dominates the communication in the classroom 63,4% and students 36,6%. The findings indicate that the non-delivery of learning is the main problem of students' lack of understanding of the material, lack of students' ability to think critically, and responsiveness to students. These findings can be used to develop more inclusive and effective teaching strategies that pay attention to a more balanced distribution of talk time and interaction between teachers and students. This research contributes to the literature on Classroom Discourse Analysis by filling the knowledge gap on the classroom's interaction pattern and its implications for teaching practices with feedback in IRF. The results of this study can provide valuable insights for educational practitioners and help improve students' critical communication strategies in the classroom.